(untitled) (Global Journal of Human-Social Science, 2021)
Teenage Pregnancy and adolescent motherhood in Sierra Leone has been increasing and is one of the world’s highest rates leading to girls dropping out of school. Some pregnant teens were asked out of school, while others bow to societal pressure and self-isolate before they are visibly identified as pregnant. Ensuring they have access to education is vital for achieving gender equality and empowering women and girls. This seems to be a priority for the government by the introduction of the Free Quality Education in 2018 and the "Radical Inclusion Policy" targeting these vulnerable girls ensuring their human rights are upheld and achieving inclusive development, as recognized in the international development agenda, the Sustainable Development Goals (SDG) 4 and 10. ( UN-SDG, 2015) This study/research looked at the barriers to educational opportunities for adolescent mothers in two districts in Sierra Leone, with the case study of Lokomassama chiefdom, Port Loko district, Northwest and Bumpe Ngao chiefdom Bo district, and southern province.